Clinical investigation of PPR outbreak and sero-prevalence of PPR viral antibody in different areas of Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
Peste des petits ruminants (PPR) is an acute, highly contagious, world organization for animal health (OIE) notifiable and economically important transboundary viral disease of sheep and goats associated with high morbidity and mortality and caused by PPR virus. This research work was done in 2016-2017 by executing, surveillance and clinical investigation studies to determine present status of circulating PPR virus and its detection of antibody level of PPRV in different areas of Bangladesh. cELISA was conducted to detect the PPR antibody and RT-PCR also used for identification of N gene PPRV. The clinical outbreak of PPR, the total 124 samples was collected at the six  locations of the country and highest case fatality (morbidity) was recorded at Jhenaidah 93.75% (75 out of 80).The highest morbidity rate and mortality rate was 69.23% and 13.07% respectively. The result of RT-PCR indicates the PPR virus circulating in the different regions of Bangladesh. For sero-prevalence of PPR antibodies of 366 serum samples were collected at different region of Bangladesh such as Chuadanga 47.81% (22 out of 47), Sirajganj 34.21% (13 out of 38), Thakurgaon 48.15% (26 out of 54), Satkhira 56.92%  (37out of 65), Jhenaidah  33.33% (28 out of 84) and Chattogram 30.79 % (24 out of 78). It is reflected that the selected areas are highly suspected PPR and need to proper vaccination against PPR vaccine that can protect PPR disease in goat and sheep which helps to meet global PPR control strategy as well as contribute to achieve the two (2) number of Sustainable Development Goals (SDGs).Asian Australas. J. Biosci. Biotechnol. 2019, 4 (2), 109-115